INVESTIGATING REPRESENTATIONS AND CAUSES OF LINGUISTIC INSECURITY IN MÊRGESORÎ SPEECH COMMUNITY/ ERBIL - Muhammad, Leila; Muhammad , Himdad (Humanities Journal of University of Zakho, 2025)
Linguistic insecurity as a mental and emotional construct can be realized in various forms. The current study deals with seven manifestations and causes of this sociolinguistic phenomenon in Mêrgesor District of the Kurdistan Region of Iraq. In the literature, no studies have examined linguistic insecurity as an intralinguistic phenomenon among the speakers of the Kurdish varieties in the region. Besides, the relatively small population in Mêrgesor District speaks a variety of Badînî subdialect, called Mêrgesorî, while it is dependent on the domineering Soranî subdialect for education and administration. Such imbalances and dependences can always shape language attitudes that control individuals’ linguistic behavior. The study employs a questionnaire and semi-structured interview as tools. The participants are 135 Mêrgesorî speakers and four language experts from the area. The findings of the study reveal that out of the seven linguistic insecurity forms only one is not found in the community. One of these forms, i.e., feeling guilty for code-switching, is an original manifestation that had no reference in the literature. The results also reveal that mostly the social factors, along the linguistic purism and essentialism ideologies, should be blamed for the persistence of linguistic insecurity in the community. The current study is important in the sense that it shows how language attitudes regulate the linguistic performance of Mêrgesorî speakers in different situations and domains. It also reinforces the previous studies over the existence of a diglossic situation in the Kurdistan Region of Iraq.